Analisi Komunikasi Circle Pertemanan Siswa Dalam Perubahan Konsep Diri - Sri Novita; Fifi Hasmawati; Hartika Utami Fitri (CV. ITTC INDONESIA, 2023)
This study aims to determine how interactions that occur in friendship circles provide changes in the self-concept of high school students. The friendship environment is one of the supporting factors in the development of students' self-concept. Basically, the self-concept becomes a form of individual reference in positioning themselves in an environment, and the friendship circle enters into an important part of the formation of the self-concept in high school students who are members of the circle formation environment. The research method used is a qualitative method with data collection techniques through interviews, observation, and documentation. As for the results of this study, they show that the self-concept of students who have joined the friendship circle does experience changes in their self-concept so as to form changes in their attitudes and behavior while in their circle environment, and this is due to a sense of confidence among individuals in the friendship circle.